State crime : governments, violence and corruption governments, violence and corruption - Green, Penny, 1957-; Ward, Tony, 1957- (London ; Sterling, Va. : Pluto Press, 2004)
What is state crime? This work defines the parameters of state crime in all its forms and highlights the complex issues involved.
Defining the State as Criminal -- Corruption as State Crime -- State-Corporate Crime -- Natural Disaster as State Crime -- Police Crime -- Organised Crime and the 'Deep State' -- State Terror and Terrorism -- Torture -- War Crimes -- Genocide -- The Political Economy of State Crime -- Every Crime in the Book: Iraq and its Liberators.
Includes bibliographical references (pages 219-250) and index.
Keywords: Political corruption; Political persecution; State crimes; State-sponsored terrorism; Genocide; War crimes; Genocide; Political corruption; Political persecution; State crimes; State-sponsored terrorism; War crimes; Staten; Overheid; Misdrijven; Geweld; Corruptie; Staatsorgan; Straftat